Self-Management of Diabetes Mellitus among Tamils in the Batticaloa District, Sri Lanka: A Qualitative Study - Kisokanth, G.; Prathapan, S.; Indrakumar, J.; Joseph, J. (My University, 2016)
The poor lifestyles, rapid urbanization, lack of knowledge, unsatisfactory attitude and practices among patients with Diabetes Mellitus (DM) have resulted for the steady increase in the prevalence of DM in Asian countries. Thus, this study aimed to explore the experiences of physicians and nutritionists on the attitudes of the patients with DM and acceptable practices on self-management of DM. Descriptive qualitative methodology was used to explore the experiences of voluntarily recruited physicians and nutritionists those who had managed the Tamil patients with DM. In-depth interviews including audio recording were used for data collection and verbatim transcripts were analyzed on the basis of content analysis. Three main themes were emerged from the content analysis of interview transcripts. Ignorance of diet habits, changing of lifestyle and healthy eating were the concerns of the health care professional. Ignorance, dietary habits and lifestyles have impacted much among Tamil patients on Self- management of DM. Change in attitudes, modification in lifestyles along with good adherence to acceptable practices would contribute to better self-management of DM among Tamils.
Keywords: Practices; attitudes; Self-management; diabetes mellitus